Analyzing the nexus of higher education and vocational training in Europe : a comparative-institutional framework - Powell, Justin J. W. [Verfasser]; Solga, Heike [Verfasser] (My University, 2010)
"Given ongoing economic, political and social transformation, skill formation systems are under pressure to change. This is acknowledged in European declarations - Bologna for higher education and Copenhagen for vocational training - and various national reform processes. The omnipresent convergence hypothesis is that these international pressures will result in national skill formation systems becoming more similar. However, if these systems throughout Europe are to match the dominant anglophone models, which value general higher education more than specific vocational training, those countries with strong apprenticeship traditions are especially challenged. Due to countries' differential starting points, the convergence hypothesis needs to be tested, taking the shifting complementary and competitive relationship between the two organizational fields of higher education and vocational training into account. Ideational internationalization, and normative and regulative Europeanization, as manifest in the Bologna and Copenhagen processes, require analysis as factors driving institutional change in post-secondary higher and vocational educational systems. Key questions are: will common trends and challenges lead to cross-national convergence of skill formation systems? Or do national responses instead indicate that adaptations are mainly consistent with specific cultural and structural characteristics? This article discusses why, in order to answer such questions adequately, in-depth comparative research should overcome the persistent division in research on these two sectors by examining the nexus of higher education and vocational training." (Autorenreferat, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.4 Hochschulbildung; T 1.5 International vergleichende Berufsbildungsforschung; Berufsbildung; Hochschulbildung; Internationalisierung; Konvergenz; Europäischer Bildungsraum; Interkulturelle Faktoren; Europa